A practical guide to decontamination in healthcare - McDonnell, Gerald E. (John Wiley & Sons, 2012)
Prevention is the first line of defence in the fight against infection. As antibiotics and other antimicrobials encounter increasing reports of microbial resistance, the field of decontamination science is undergoing a major revival. A Practical Guide to Decontaminationin Healthcare is a comprehensive training manual, providing practical guidance on all aspects of decontamination including: microbiology and infection control; regulations and standards; containment, transportation, handling, cleaning, disinfection and sterilization of patient used devices; surgical instrumentation; endoscopes.